TRAFFIC SIMULATION TRAFFIC SYSTEM USING SIMEVENTS MATLAB - ERWIN (INFOKOM (Informatika & Komputer), 2018)
Road traffic is a supporting medium that is essential to various means of land transportation that connect various locations and even large cities. Smooth traffic is a good parameter of the management of a city, also as a sign to determine the technological and economic development in the city. As the rate of civilization grows, as well as the number of people, the road traffic becomes more crowded, so that, congestion occurs to an alarming level. The solution to breaking down the congestion problem is by applying some methods and traffic engineering. However, implementing some methods and traffic engineering without proper planning, will lead to high costs and less optimal results. In this article we proposed a traffic simulation system called as "LINTAS", as a tool in trying to decipher the traffic jam. The exact method and traffic engineering, before it is tested in a real way, is first simulated through the LINTAS system, so that it can be known its effectiveness. LINTAS are built using the SimEvents toolbox and run on MATLAB-Simulink software. The LINTAS simulator is performed based on the mathematical sciences, especially the field of queueing theory.